Optimizing the Performance of the Serdang Bedagai Police in Overcoming Traffic Incidents - Nainggolan, Parlin; Zulyadi, Rizkan; Frensh, Wenggedes (Journal of Public Representative and Society Provision, 2025)
Traffic accidents are a serious problem that affects public safety and has a significant social and economic impact. This study aims to analyze the optimization of the performance of the Serdang Bedagai Police in overcoming traffic accidents in its jurisdiction. The research method used is qualitative with a descriptive approach. Data were obtained through interviews, observations, and documentation studies which were then analyzed in depth. The results of the study show that the main factors causing traffic accidents in Serdang Bedagai Regency are human factors, vehicle factors, and environmental factors. The Serdang Bedagai Police have made various efforts in dealing with traffic accidents, which include preventive, repressive, and rehabilitative approaches. Preventive efforts are carried out through socialization and driving safety education to the public. Repressive efforts are carried out through law enforcement such as electronic ticketing (ETLE) and vehicle raids, while rehabilitative efforts involve coordination with hospitals and psychological assistance for accident victims. Despite various efforts, this study found the main challenges faced, such as the lack of police personnel, low public awareness, and inadequate road infrastructure. Therefore, cooperation between the police, local governments, and the community is needed to improve traffic safety. With good synergy, it is hoped that the number of traffic accidents in Serdang Bedagai Regency can continue to decrease.